Online press and banking performance in a controlled media landscape: Evidence from Vietnam - Phung, Thi Lan Nhi; Le, Chi Dat (Asian Economic and Financial Review, 2025)
This study examines the impact of digital press coverage on the performance of Vietnamese banks by extending asymmetric information and signaling theories within a controlled media landscape. Using Scrapy to crawl 35 online outlets (2013–2023), we extracted 181,430 articles mentioning 30 Vietnamese banks. We analyzed these articles using sentiment analysis and the VADER dictionary to construct metrics for media coverage and tone. We employed the Fractional Logit model to regress bank efficiency (measured by DEA) on bank coverage and media tone variables. The findings indicate that increased bank visibility in newspapers improves efficiency, as media coverage reduces information asymmetry and enhances transparency. Additionally, bad news, particularly negative coverage from state-owned media and non-financial newspapers, negatively influences banks' performance compared to positive information. These results remain robust after controlling for endogeneity. Given the significant influence of state-owned media in Vietnam, this study offers practical implications for policymakers to utilize state-owned media as a tool to improve bank efficiency and maintain financial stability. Local newspapers, being more accessible to the general public, can also be leveraged by banks to disseminate information and provide transparency about their financial situation, helping to increase public trust and mitigate negative coverage.